Evaluation of awareness of job responsibilities and incentives of accredited social health activist in the delivery of health care services - Panda, Mayadhar; Nanda, Sikata (International Journal Of Community Medicine And Public Health, 2018)
Background: Accredited social health activist (ASHA) workers are the female health volunteers of the community who takes steps to generate awareness and provide information to the community on determinants of health such as nutrition, hygiene practices and basic sanitation, healthy living condition. Our aim was to evaluate the level of awareness of job responsibilities of ASHA workers, to assess about their awareness about the different incentives in the delivery of health care services and to recommend for improvement on the functioning of the ASHA workers. Methods: A cross sectional study was conducted in Khordha district of Odisha from March 2018 to July 2018. 3 blocks were selected purposively i.e. Bhubaneswar under urban block, Bolagarh under rural block and Banapur a tribal block. Working in the 3 selected blocks, 331 ASHA’s participated in the study. Results: 37% were between 34-39 years and 30% were in the age group of 34-39 years in the rural block and about 40% ASHA workers belonged to 25-29 years of age. For full immunization in the 1st year of life per beneficiary an amount of Rs. 100 is given to an ASHA worker. However, 67 (68.4%) in urban block, 79 (63.2%) in rural block and 83 (76.8%) ASHAs in tribal block were aware about this incentive. Conclusions: The role of ASHAs should be well defined and accordingly with supportive supervision, the ASHAs should be monitored to efficiently & effectively play their roles and discharge duties.